2022
DOI: 10.3389/fonc.2022.917054
|View full text |Cite
|
Sign up to set email alerts
|

The addition of radiotherapy to breast-conserving surgery improves survival for elderly patients with early breast cancer

Abstract: PurposeTo evaluate whether adjuvant radiotherapy (RT) after breast-conserving surgery (BCS) was associated with better survival among elderly (≥70 years) breast cancer patients with T1-2N0 and estrogen receptor (ER) positive disease.MethodsWe included patients who met the inclusion criteria between 2010 and 2014 from the Surveillance, Epidemiology, and End Results program. Patients were subdivided into three groups based on surgery and RT: BCS alone, BCS plus RT, and refusal of RT. The primary outcomes were br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…In our study, the proportion of patients aged ≥ 70 years with T1-T2N0 ER-negative breast cancer who received RT after BCS was not significantly different from 2010 to 2015 (P = 0.182). Moreover, we found that age, marital status, tumor grade, and HER2 status were the main factors associated with RT decision, which is consistent with previous clinical practice [ 15 , 16 ]. Numerous studies have demonstrated that older breast cancer patients with ER-negative tumors have higher rates of recurrence and breast cancer-specific mortality [ 17 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the proportion of patients aged ≥ 70 years with T1-T2N0 ER-negative breast cancer who received RT after BCS was not significantly different from 2010 to 2015 (P = 0.182). Moreover, we found that age, marital status, tumor grade, and HER2 status were the main factors associated with RT decision, which is consistent with previous clinical practice [ 15 , 16 ]. Numerous studies have demonstrated that older breast cancer patients with ER-negative tumors have higher rates of recurrence and breast cancer-specific mortality [ 17 19 ].…”
Section: Discussionsupporting
confidence: 90%
“…This finding indicates that the benefits of OS from post-BCS RT extend beyond just the luminal subtypes and apply to basal-like and HER2-enriched breast cancers. The lack of tumor control in basal-like and HER2-enriched breast cancers did not diminish the OS benefits of post-BCS RT, suggesting that RT has a robust effect on prolonging survival in post-BCS patients [ 5 , 44 , 45 ]. It is a proven fact that post-BCS RT has noticeable positive effects on breast cancer patients, with both breast-cancer-specific survival and OS significantly improved even in elderly patients (age ≥ 70 years) [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of tumor control in basal-like and HER2-enriched breast cancers did not diminish the OS benefits of post-BCS RT, suggesting that RT has a robust effect on prolonging survival in post-BCS patients [ 5 , 44 , 45 ]. It is a proven fact that post-BCS RT has noticeable positive effects on breast cancer patients, with both breast-cancer-specific survival and OS significantly improved even in elderly patients (age ≥ 70 years) [ 44 ]. Furthermore, the benefits of RT on OS were not dependent on irradiation volume, as similar benefits were observed in patients who underwent accelerated partial breast irradiation and those who received whole breast RT [ 46 ].…”
Section: Discussionmentioning
confidence: 99%